Transforming Growth Factor-β-Induced KDM4B Promotes Chondrogenic Differentiation of Human Mesenchymal Stem Cells. (17th November 2015) - Lee, Hye-Lim; Yu, Bo; Deng, Peng; Wang, Cun-Yu; Hong, Christine
Abstract: The high prevalence of cartilage diseases and limited treatment options create a significant biomedical burden. Due to the inability of cartilage to regenerate itself, introducing chondrocyte progenitor cells to the affected site is of significant interest in cartilage regenerative therapies. Tissue engineering approaches using human mesenchymal stem cells (MSCs) are promising due to their chondrogenic potential, but a comprehensive understanding of the mechanisms governing the fate of MSCs is required for precise therapeutic applications in cartilage regeneration. TGF-β is known to induce chondrogenesis by activating SMAD signaling pathway and upregulating chondrogenic genes such as SOX9; however, the epigenetic regulation of TGF-β-mediated chondrogenesis is not understood. In this report, we found that TGF-β dramatically induced the expression of KDM4B in MSCs. When KDM4B was overexpressed, chondrogenic differentiation was significantly enhanced while KDM4B depletion by shRNA led to a significant reduction in chondrogenic potential. Mechanistically, upon TGF-β stimulation, KDM4B was recruited to the SOX9 promoter, removed the silencing H3K9me3 marks, and activated the transcription of SOX9 . Furthermore, KDM4B depletion reduced the occupancy of SMAD3 in the SOX9 promoter, suggesting that KDM4B is required for SMAD-dependent coactivation of SOX9. Our results demonstrate the critical role of KDM4B in the epigenetic regulation of TGF-β-mediated chondrogenic differentiation of MSCs. Since histone demethylases are chemically modifiable, KDM4B may be a novel therapeutic target in cartilage regenerative therapy. Abstract : Epigenetic regulation of TGF-directed chondrogenesis and its future in cartilage regeneration